Digital Transformation in Fundraising Zakat, Infak, and Sedekah: A Study of Technology Utilization at Nu Care Lazisnu Cilacap - Chamid, Abdul; Habeeb, Emiola; Zaenal Mutaqin, Enjen (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
The use of digital technology in optimizing the collection of zakat, infaq, and alms funds at NU Care LAZISNU Cilacap is the main focus of this study. The existence of a digital-based payment system is related to transactions that takes place at zakat, infaq, and alms outlets. When compared, the use of the internet provides greater advantages, due to the wider coverage of muzakki and faster access. The management of this system also requires high professionalism by considering various aspects so that the results achieved can be maximized. Along with the increasing penetration of the internet in daily life, the Amil Zakat Infak and Sadaqah Nahdlatul Ulama (LAZISNU) Institution of Cilacap Regency does not stay silent. NU Care LAZISNU Cilacap proactively develops innovations in the management of zakat based on digital technology, thereby making it easier for muzakki to make transactions. This research aims to explore the role of digital technology in the fundraising process at NU Care LAZISNU Cilacap and its impact on increasing zakat collection. This study uses a qualitative approach with a field study method. Data collection techniques include observation, interviews, and documentation. Data reduction techniques, data presentation, and conclusion drawn carry out data analysis. The results of the study show that the application of digital technology in the management of zakat, infaq, and alms fundraising at NU Care LAZISNU Cilacap is in accordance with the underlying theory. The implementation of the concept of roles, characteristics of digital technology, and the use of the internet in the form of the NU Care LAZISNU Cilacap website, social media, and other supporting applications are important elements in a more effective zakat fundraising system. This study examines the utilization of digital technology in optimizing the collection of zakat, infaq, and sadaqah at NU Care LAZISNU Cilacap. Using a qualitative field study approach, data were collected through observation, interviews, and documentation. The findings reveal that digital platforms such as websites, social media, and QRIS-based applications significantly increase fundraising efficiency and transparency. The study concludes that technology adoption strengthens public trust and expands donor reach.